Electronic Word of Mouth and Sales Promotion as Drivers of Purchase Decision: The Mediating Role of Perceived Value among Generation Z Consumers of Glad2Glow Products - Difa Putri Salsabila; Restu Frida Utami; Muchammad Agung Miftahuddin; Ika Yustina Rahmawati (Dinasti Review, 2026)
The rapid growth of the beauty industry in Indonesia demands a thorough understanding of consumer behavior and effective marketing strategies, particularly for products that are popular among Generation Z, such as Glad2Glow. This study aims to analyze the influence of electronic word of mouth (E-WOM) and sales promotion on the purchase decision of Glad2Glow products in the marketplace, with perceived value as a mediating variable. A quantitative approach was employed, with primary data collected through a 5-point Likert scale questionnaire. The sample was selected using purposive sampling, comprising 210 Generation Z respondents (aged 17–28) in Purwokerto who had purchased Glad2Glow products on the marketplace within the last six months. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0. The results indicate that all hypotheses were supported. Specifically, both E-WOM and sales promotion have a positive and significant influence on purchase decision and perceived value. Moreover, perceived value was found to positively and significantly influence purchase decision. Importantly, perceived value was confirmed to mediate the influence of E-WOM and sales promotion on purchase decision.